Manejo de Scaptotrigona Sp. (Hymenoptera, Apidae, Meliponini) para polinização da rambuteira (Nephelium Lappaceum L.) - LEÃO, Kamila de Sousa (Universidade Federal do Pará, 2017)
Meliponini bees can be easily kept and they are important crop pollinators. This study aimed to manage a Scaptotrigona species to improve pollination in rambutan trees (Nephelium lappaceum L.). The first chapter analysed the phenological development (flowering and fruit phases) in rambutan crop. Two blossom periods per year were identified. The average cycle duration (from anthesis to harvest fruit point) was 123-128 days. The objective of the second chapter was evaluate the effect of Scaptotrigona sp. nests in rambutan fruit set. There were not significantly differences on rambutan fruit set upon bee presence or absence, although Scaptotrigona sp. presented high index of pollen fidelity to rambutan. The last chapter focused on a specific question about stingless beekeeping. It was tested whether a rational hive model (Embrapa) was better than a traditional hive (cabocla) for Scaptotrigona sp. management, by evaluating certain aspects, such as biological adaptation and management, . It was found that the studied hive (Embrapa) is a suitable model to rational creation of Scaptotrigona.